Interdisciplinary Approaches Suggested for Children With Multiple Hospital Referrals Presenting With Non-specific Conditions - Elgen, Irene; Lygre, Ragnhild; Greve, Gottfried; Griffiths, Silja; Heggestad, Torhild (Frontiers in Pediatrics, 2021)
Aims: To describe the care patterns of patients with repeated referrals to both mental and somatic specialist healthcare, and to study their diagnostic processes. Methods: From a previous register study of 18 577 patients aged 6–12 years referred to Haukeland University Hospital from 2013 to 2015, we found 922 children with at least three referrals including both somatic and mental health services. Of these, 250 were randomly selected and observed from their first hospital episode ever and followed up after inclusion during their next three referrals or until July 2017. Data on referral patterns and diagnostics were collected from patient records. Results: Mean number of referrals was 6.5 prior to inclusion and 4.2 in the follow-up period. At the end of the study period 15% of patients still had a non-specific diagnosis. During the follow-up period, more than half of the children were again referred across the border between somatic and mental healthcare. Conclusion: Very complex care patterns were found for these patients, repeatedly being referred and “crossing over” between mental and somatic healthcare. This indicates a need for more interdisciplinary-based approaches both within specialist care and between care levels in public health management to broaden the perspective and achieve shorter time lag before reaching a diagnostic conclusion.